Investigation of Liquefaction in Balaroa, Petobo, and Jonooge (Central Sulawesi, Indonesia) Caused by the 2018 Palu Earthquake Sequence - Triyono, Rahmat; Widiyantoro, Sri; Zulfakriza, Zulfakriza; Supendi, Pepen; Rahman, Aditya Setyo; Gunawan, Mohamad Taufik; Oktavia, Nur Hidayati; Rahmatullah, Fajri Syukur; Fadhilah, Fildzah Zaniati; Habibah, Nur Fani; Sativa, Oriza; Permana, Dadang; Wallansha, Robby; Octantyo, Ardian Yudhi; Persada, Yoga Dharma; Pranata, Bayu; Sujabar, Sujabar (Journal of Engineering and Technological Sciences, 2024)
The liquefaction that occurred in the city of Palu on September 28, 2018, was caused by a series of significant earthquakes that took place in a relatively short time around 25 minutes after the main earthquake of magnitude 7.5. This event was followed by aftershocks of magnitudes 6.4, 6.2, and 6.1. The magnitude 6.2 aftershock occurred at 10.16 UTC, while the magnitude 6.1 aftershock occurred at 10.25 UTC. These were both located very close to the liquefaction locations in Balaroa, Petobo, and Jono Oge. We investigated the mainshock and the three aftershocks using the NCEER method based on Vs30 measurements and data from the drill liquefaction locations at Balaroa, Petobo, and Jono Oge. We found that the liquefaction was not only caused by the main earthquake but also by the subsequent aftershocks that occurred within 25 minutes after the mainshock.